2013
DOI: 10.1007/s00127-013-0724-9
|View full text |Cite
|
Sign up to set email alerts
|

The societal cost of bipolar disorder in Sweden

Abstract: The high cost of bipolar disorder is driven primarily by indirect costs. Costs were strongly associated with mood episodes, hospitalisations and low GAF scores. This suggests that treatment that reduces the risk for relapses and hospitalizations and improve functioning may decrease both the societal cost of bipolar disorder and patient suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 24 publications
2
35
0
5
Order By: Relevance
“…In Germany the total annual cost was calculated to be 5.8 million euros, with 98% being due to productivity loss (Runge and Grunze, 2004). Similar estimations come from other areas of the world, with the calculations basing on different prevalence rates and health systems and societal structures (Hakkaart-van Roijen et al, 2004; Fisher et al, 2007; Ekman et al, 2013). …”
Section: Introductionmentioning
confidence: 53%
“…In Germany the total annual cost was calculated to be 5.8 million euros, with 98% being due to productivity loss (Runge and Grunze, 2004). Similar estimations come from other areas of the world, with the calculations basing on different prevalence rates and health systems and societal structures (Hakkaart-van Roijen et al, 2004; Fisher et al, 2007; Ekman et al, 2013). …”
Section: Introductionmentioning
confidence: 53%
“…Hospitalization costs associated with manic episodes ranges from 50% to up to 80% of total direct expenses. 19,20,22,23 Furthermore, in our study patients who had been hospitalized needed more outpatient appointments after discharge.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study from Sweden reports that incidence and prevalence of BD has increased during the last 20 years [5]. BD entails a significant burden for those that are affected as well as high societal costs related to health care, sick leave and early retirement [6]. The Swedish study has found that in persons with BD, despite similar education levels, employment levels are lower and disposable income is less compared to the general population.…”
Section: Introductionmentioning
confidence: 99%